2001
DOI: 10.1007/s001090100204
|View full text |Cite
|
Sign up to set email alerts
|

Shock waves: a novel method for cytoplasmic delivery of antisense oligonucleotides

Abstract: Intracytoplasmic delivery of oligonucleotides (ODN) can improve ODN-based strategies such as the antisense approach and the use of immunostimulatory CpG dinucleotide containing ODN. Shock waves are established for the treatment of nephrolithiasis and other diseases. Here we describe the use of shock waves as a new physical method for the direct transport of antisense ODN into the cytoplasm and the nucleus of cells. Human peripheral blood mononuclear cells together with antisense ODN were exposed to shock waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The possibility that the effects of laser irradiation are in part mediated by changes in plasmamembranes may be supported by observations that shock waves, another kind of mechanical biostimulation, increase substance uptake and delivery via membrane modulation [29,32].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that the effects of laser irradiation are in part mediated by changes in plasmamembranes may be supported by observations that shock waves, another kind of mechanical biostimulation, increase substance uptake and delivery via membrane modulation [29,32].…”
Section: Discussionmentioning
confidence: 99%
“…38 When the energy deposited by the lithotripter is reduced below the lethal value, it is possible to permeabilize the cells without killing them. [42][43][44][45][46] In this way, molecules present in the surrounding medium can diffuse into the cells. This effect has possible applications for drug delivery and gene transfer.…”
Section: Shock Waves Produced By Lithotriptersmentioning
confidence: 99%
“…In vivo and in vitro studies revealed that shock waves may cause transient cell permeabilization, allowing large molecules (normally excluded by the cell membrane) to become trapped inside the cell, opening the possibility of shock wave drug delivery and gene transfection (Gambihler et al 1994 ;Lauer et al 1997 ;Bao et al 1998 ;Tschoep et al 2001 ;Schaaf et al 2003 ;Doukas and Fig. 21.1 Sketch of a pressure waveform recorded at the focus of a shock wave generator, showing the peak positive pressure p + , the peak negative pressure p − , the rise time and the full-width-half-maximum.…”
Section: Theoretical Backgroundmentioning
confidence: 99%